Hubungan Conscientiousness Personality dan Peer Conformity dengan Prokrastinasi Pada Mahasiswa PGSD FIP UMJ - Aulia Adeline; Ahmad Susanto (JURNAL PSIKOLOGI INSIGHT, 2022)
This research aims to investigate the relationship of conscientiousness personality and peer conformity to procrastination among students in the PGSD (Elementary School Teacher Education) program at FIP UMJ (University of Muhammadiyah Jakarta). The research method employed is a quantitative correlational approach. The population in this study consists of all active students in the 2018 cohort of PGSD FIP UMJ. A sample of 154 students was selected for the study. Hypothesis testing was carried out using the Pearson Product Moment technique after conducting assumption tests, which included tests for normality and linearity of the regression. .The results of the data analysis reveal that the Pearson coefficient for the conscientiousness personality variable is 0.678, and for the peer conformity variable, it is 0.744, both with a significant value of 0.000. This indicates a positive relationship between conscientiousness personality and peer conformity with procrastination. The findings of this research show that conscientiousness personality and peer conformity contribute to procrastination by 55.5%, while the remaining 44.5% is influenced by other unexamined factors.Penelitian ini bertujuan untuk mengetahui hubungan conscientiousness personality dan peer conformity dengan prokrastinasi pada mahasiswa PGSD FIP UMJ. Metode penelitian yang digunakan adalah kuantitatif korelasional. Populasi dalam penelitian ini adalah seluruh mahasiswa aktif PGSD FIP UMJ angkatan 2018. Sampel yang diambil berjumlah 154 mahasiswa. Pengujian hipotesis dilakukan dengan teknik Pearsonâ€™s Product Moment setelah dilakukan uji asumsi yang terdiri dari uji normalitas dan linieritas hubungan. Hasil analisis data menunjukkan koefisien Pearson variabel conscientiousness sebesar 0,678 dan variabel peer conformity sebesar 0,744 dengan angka signifikan 0,000Â  yang berarti terdapat hubungan positif antara conscientiousness personality dan peer conformity terhadap prokrastinasi. Hasil penelitian ini menunjukkan sumbangan yang diberikan conscientiousness personality dan peer conformity terhadap prokrastinasi adalah sebesar 55,5 persen sisanya sebesar 44,5 persen dipengaruhi oleh faktor lain yang tidak diteliti. Dari hasil penelitian ini dapat ditarik kesimpulan bahwa hipotesis penelitian dapat diterima.